Educommunication: a theoretical approach of studying media in school environments - Mateus, Julio-César (2017)
Edu-communication is a field of study founded by the Latin American theoretical currents of liberating pedagogy, popular communication and cultural studies. This essay reviews their foundation and recent theoretical development in Peru. The three fundamental contributions of edu-communication are as follows: recognizing inter-subjectivity as being a critical element for understanding the interactions between individuals and media, the attention assigned to cultural communicative practices and political dimensions, and its focus on the individual rather than on the technological device, deviating from the more instrumental theoretical perspectives.